2022
DOI: 10.3389/fbioe.2022.907589
|View full text |Cite
|
Sign up to set email alerts
|

Role of chitosan in titanium coatings. trends and new generations of coatings

Abstract: Survival studies of dental implants currently reach high figures. However, considering that the recipients are middle-aged individuals with associated pathologies, research is focused on achieving bioactive surfaces that ensure osseointegration. Chitosan is a biocompatible, degradable polysaccharide with antimicrobial and anti-inflammatory properties, capable of inducing increased growth and fixation of osteoblasts around chitosan-coated titanium. Certain chemical modifications to its structure have been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 138 publications
0
8
0
Order By: Relevance
“…[ 84 ] In addition, this nanocarrier protects the drug from degradation during administration and maintains drug release, thereby increasing half‐life and bioavailability. [ 63b ] For example, in a delivery system consisting of chitosan and the natural AMP LL37 (CS/LL37‐NPs), the release of LL37 from CS/LL37‐NPs was almost complete after 5 days according to the in vitro release profile. Furthermore, this delivery system has a prolonged half‐life.…”
Section: Abdominal Infectionmentioning
confidence: 99%
“…[ 84 ] In addition, this nanocarrier protects the drug from degradation during administration and maintains drug release, thereby increasing half‐life and bioavailability. [ 63b ] For example, in a delivery system consisting of chitosan and the natural AMP LL37 (CS/LL37‐NPs), the release of LL37 from CS/LL37‐NPs was almost complete after 5 days according to the in vitro release profile. Furthermore, this delivery system has a prolonged half‐life.…”
Section: Abdominal Infectionmentioning
confidence: 99%
“…Fluorine(F),zinc(Zn),calcium (Ca),copper(Cu),cerium (Ce),chloride (CI)and iodine (I)ions can be loaded onto the titanium-based metal surface by anodic oxidation [3]. The antibacterial mechanism of ionic coating may be: (1) (2)generation of reactive oxygen species to oxidize with the bacterial cell membrane,increasing the permeability of the cell membrane;(3)free ions are absorbed by the bacterial cell membrane,and are combined with proteins and nucleic acids containing sulfhydryl (-SH),amino(-NH)and carboxyl (-COOH)groups in the cytoplasm. Liu et al compared pure titanium with titaniumcopper implants in vitro experiments and found that titanium-copper alloy had stronger antibacterial activity against Streptococcus mutans and Porphyromonas gingivalis,and cell proliferation and adhesion tests using mesenchymal stem cells showed that titanium-copper alloy had similar biocompatibility to pure titanium.…”
Section: Antibiotic and Organic Antimicrobial Coatingsmentioning
confidence: 99%
“…In the 1850s Branemark implanted optical speculums made of titanium into the tibia and fibula of rabbits in vivo microscopic observation [1]. At the end of the experiment,the implanted speculum was firmly bonded to the surrounding bone tissue and could not be removed;Branemark called this phenomenon osseointegration and began to study the use of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…One solution for the airborne pollutants that threaten human health is to develop antimicrobial filter materials that can remove bioaerosols. Antimicrobial coatings impart surfaces with the ability to inactivate pathogens , and can be achieved by impregnating a filter surface, covalently or noncovalently, with various biocides, e.g., metal ion, , metal oxides, , and chitosan (CS). , Metal or metal oxide coatings can have various adverse effects to the environment as well as to human beings. For example, previous studies showed that silver nanoparticles are permeable to skin and thus toxic to mammalian organs .…”
Section: Introductionmentioning
confidence: 99%